(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Mathematics is practicing explicitly and implicitly as a part of everyday activity of different group of people. The intent of this paper is to analyze the mathematical ideas practiced in the out-of-school environment and its possible connection to the teaching and learning of school mathematics. The mathematical thinking and ideas used by the different professional groups of people, such as carvers, mason, carpenter, street venders, black smith, gold smith, shoe makers, children’s games, cultural arts, cultural artefacts and household activities are limited by their workplace boundaries. Viewing their boundaries from outside, these professional groups of people is using mathematical knowledge and ideas just to perform their everyday activities. The connection of the mathematical ideas practiced in out-of-school context to the school mathematics helps students understand mathematics in effective and meaningful ways. Understanding the mathematical ideas embedded in out-of-school activities can enhance students’ grasp of formal mathematics by connecting these practical experiences to academic concepts. Bridging the gap between everyday mathematical practices and school-based instruction can make learning more relevant and engaging, helping students see the real-world applications of their mathematical knowledge.